De novo Biosynthesis of Odd-Chain Fatty Acids in Yarrowia lipolytica Enabled by Modular Pathway Engineering - Park, Young-kyoung; Ledesma-Amaro, Rodrigo; Nicaud, Jean-Marc (Frontiers in Bioengineering and Biotechnology, 2020)
Microbial oils are regarded as promising alternatives to fossil fuels as concerns over environmental issues and energy production systems continue to mount. Odd-chain fatty acids (FAs) area type of valuable lipid with various applications: they can serve as biomarkers, intermediates in the production of flavor and fragrance compounds, fuels, and plasticizers. Microorganisms naturally produce FAs, but such FAs are primarily even chain; only negligible amounts of odd-chain FAs are generated. As a result, studies using microorganisms to produce odd-chain FAs have had limited success. Here, our objective was to biosynthesize odd-chain FAs de novo in Yarrowia lipolytica using inexpensive carbon sources, namely glucose, without any propionate supplementation. To achieve this goal, we constructed a modular metabolic pathway containing seven genes. In the engineered strain expressing this pathway, the percentage of odd-chain FAs out of total FAs was higher than in the control strain (3.86% vs. 0.84%). When this pathway was transferred into an obese strain, which had been engineered to accumulate large amounts of lipids, odd-chain fatty acid production was 7.2 times greater than in the control (0.05 g/L vs. 0.36 g/L). This study shows that metabolic engineering research is making progress toward obtaining efficient cell factories that produce odd-chain FAs.